Temporal Changes in Breast Milk Fatty Acids Contents: A Case Study of Malay Breastfeeding Women - Khor, Geok Lin; Tan, Seok Shin; Stoutjesdijk, Eline; Ng, Kock Wai Tony; Khouw, Ilse; Bragt, Marjolijn; Schaafsma, Anne; Dijck-Brouwer, D. A. Janneke; Muskiet, Frits A. J. (Nutrients, 2020)
The composition of human breast milk changes in the first two months of life, adapting itself to the evolving needs of the growing new-born. Lipids in milk are a source of energy, essential fatty acids (FA), fat-soluble vitamins, and vital bioactive components. Information on breast milk FA of Malaysian lactating women is scarce. Based on convenience sampling, a total of 20 Malay breastfeeding women who fulfilled the inclusion criteria were recruited. Breast milk was collected three times from each subject at consecutive intervals of 2–3 weeks apart. A total of 60 breast milk samples were collected and classified into “transitional milk” (n = 8), “early milk” (n = 26) and “mature milk” (n = 26). All milk samples were air freighted to University of Groningen, Netherlands for analysis. The dominant breast milk FA were oleic acid, constituting 33% of total fatty acids, followed by palmitic acid (26%). Both these FA and the essential FA, linoleic acid (10%) and alpha-linolenic acid (0.4%), showed no significant changes from transitional to mature milk. Breast milk ratio of n-6:n-3 polyunsaturated fatty acids (PUFA) was comparatively high, exceeding 10 throughout the lactation period, suggesting a healthier balance of PUFA intake is needed in pregnancy and at postpartum.